2008
DOI: 10.1111/j.1440-1819.2008.01825.x
|View full text |Cite
|
Sign up to set email alerts
|

Restless legs syndrome and its relationship with insomnia symptoms and daytime distress: Epidemiological survey in Sweden

Abstract: To investigate prevalence estimates of restless legs syndrome (RLS) in relation to insomnia complaints and daytime distress a questionnaire was sent to a randomly selected sample of 1962 inhabitants of Uppsala, Sweden. The questionnaire included questions about sleep and daytime distress and the standardized four-question set for epidemiological settings recommended by the International RLS Study Group. A positive diagnosis of RLS was established in 18.8% of all responders. When the optional question about fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 10 publications
3
33
0
1
Order By: Relevance
“…RA is the most examined inflammatory disease and frequency of RLS in patients with RA range from 15% to 30% (23,24). Number of studies that examining the prevalence of RLS in chronic inflammatory connective tissue disease even more limited compared with RA (10,(12)(13)(14)(15). This association was thought to be related to inflammatory processes, iron deficiency, neurochemical predisposition arising from chronic pain, or neuropathies in rheumatologic diseases (24), although it is not certain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RA is the most examined inflammatory disease and frequency of RLS in patients with RA range from 15% to 30% (23,24). Number of studies that examining the prevalence of RLS in chronic inflammatory connective tissue disease even more limited compared with RA (10,(12)(13)(14)(15). This association was thought to be related to inflammatory processes, iron deficiency, neurochemical predisposition arising from chronic pain, or neuropathies in rheumatologic diseases (24), although it is not certain.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, sleep loss and fragmentation of sleep due to RLS has a major impact on health and daytime functioning (10). Poor restorative sleep has been connected with pain, fatigability, stress and disease activity in rheumatic disease population (11).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a Swedish questionnaire study 48 reported associations between RLS and anxiety and depression in individuals whose RLS symptoms occurred at least twice a week; no such associations were observed among individuals with infrequent symptoms (occurring less than twice a week). A Turkish study 47 showed a correlation between the severity of RLS (as assessed by the International Restless Legs Syndrome Study Group Rating Scale [IRLS]) and the severity of anxiety and depression symptoms.…”
Section: Figure 1 Odds Ratios For the Associations Between Restless mentioning
confidence: 96%
“…A high incidence of co-morbid medical conditions was also found for narcolepsy, a disorder of unknown etiology that is characterized by excessive sleepiness that typically is associated with cataplexy and other rapid eye movement (REM) sleep phenomena, such as sleep paralysis and hypnagogic hallucinations, as well as for other sleep disorders (e.g., restless leg syndrome (RLS) 15%), OSAS (25%)), obesity, cognitive deficit, psychiatric disorders (depression and anxiety), chronic pain, gastrointestinal disorders, hypercholesterolemia, and blood hypertension [11,12,13,14,15,16]. Patients with moderate to severe RLS report an increased incidence of sleep-related problems (up to 2–5 fold) [17,18], while severe RLS is frequently associated with depression, anxiety, obesity, OSAS, cardiovascular disorders, diabetes, erectile dysfunction, and end-stage renal disorders [19]. Research on twins has shown that sleep disorders often co-occur in a family in association with emotional, behavioral and health-related problems resulting from environmental rather than genetic factors [20].…”
Section: Effects Of Sleep Disordersmentioning
confidence: 99%